2007
DOI: 10.1097/01.tp.0000277599.25079.94
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation in Children With Congenital Heart Disease

Abstract: LDLT is a safe procedure in a select group of ESLD patients with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…There are case reports of iatrogenic venous air embolism, with right-to-left shunting of emboli across a PFO during LT (90,91). The overall incidence of this complication appears to be quite low (isolated case reports), and liver transplantation for the most part can be performed safely in patients with a PFO and other types of intracardiac shunts (92). Although the presence of a PFO is not a contraindication to LT, extra care should be taken to prevent thrombus formation and air entry into the venous system during surgery.…”
Section: Patent Foramen Ovalementioning
confidence: 82%
“…There are case reports of iatrogenic venous air embolism, with right-to-left shunting of emboli across a PFO during LT (90,91). The overall incidence of this complication appears to be quite low (isolated case reports), and liver transplantation for the most part can be performed safely in patients with a PFO and other types of intracardiac shunts (92). Although the presence of a PFO is not a contraindication to LT, extra care should be taken to prevent thrombus formation and air entry into the venous system during surgery.…”
Section: Patent Foramen Ovalementioning
confidence: 82%
“…End‐stage liver disease is associated with cardiovascular abnormalities such as increased cardiac output, lower systemic blood pressure, and decreased peripheral vascular resistance. However, the coexistence of end‐stage liver disease and CHD is rare in the LT setting …”
Section: Introductionmentioning
confidence: 99%
“…Raichlin et al reported the results of combined heart and liver transplantation and found no difference in survival in comparison with heart transplantation alone. However, when combined heart and liver transplantation is not an option or an indication, deciding what comes first should take into consideration the risks of worsening liver function after a cardiac repair versus the development of the aforementioned complications in a patient with heart disease . In our case, the cardiac malformation demanded early intervention.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of reports on LT and CHD involve patients with Alagille syndrome, and the usual CHDs are pulmonary stenosis and aortic stenosis . Other centers have performed deceased donor LT and living donor liver transplantation (LDLT) for patients with CHD (Table ), and some have not found an increase in morbidity or mortality . In a case‐control study, however, no correction of the heart condition was attempted before LT, and there were no intraoperative cardiac complications; this suggested that every patient had compensated heart disease at the time of LT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation